Application of Onyx for Renal Arteriovenous Malformation With First Case Report of a Renal Hyperdense Striation Sign: A CARE-Compliant Article. Issue 39 (September 2015) - Juan, Yu-Hsiang; Lin, Yu-Ching; Sheng, Ting-Wen; Cheung, Yun-Chung; Ng, Shu-Hang; Yu, Chin-Wei; Wong, Ho-Fai
Abstract : Abstract: Onyx is an emerging treatment modality for visceral vascular malformations, especially in cases in which delicate nidal penetration of the arteriovenous malformation (AVM) is desired. A computed tomography (CT) image presentation of hyperdense striations along the renal medulla secondary to the tantalum powder has not been previously reported. A 65-year-old woman presented to our institution with intermittent gross hematuria and left flank pain for 10 days. Both CT and conventional angiographies confirmed cirsoid-type renal AVM, which was successfully treated with Onyx. Follow-up CT after treatment revealed presence of hyperdense striations along the renal medulla, which resolved during later image follow-up. Despite its frequent usage in neural intervention, the application of Onyx in visceral AVM is gradually gaining interest, especially in cases in which delicate nidal penetration of the AVM is desired. Renal hyperdense striation sign should be recognized to avoid confusion with embolizer migration, and further studies in patients with renal function impairment may be helpful in understanding its influence of renal function.